2007
DOI: 10.1002/jcu.20295
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastasis of esophageal adenocarcinoma with an unusual presentation

Abstract: We describe an unusual presentation of a cutaneous metastasis of esophageal adenocarcinoma in the left tempero-parietal skull and the sonographic features that helped establish the diagnosis. The patient had a primary tumor surgically resected 4 years earlier and was in clinical remission at the time of presentation. The patient presented to our radiology department with a lump on the head after a fall, and sonographic examination was recommended to assess the presumed posttraumatic hematoma. The examination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…According to a recent report, survival differences based on histology have been observed, and the adenocarcinoma subtype had a slightly longer survival rate 16 . They suggested that the introduction of endoscopic surveillance programs for Barrett's esophagus might explain the more pronounced improvement in survival among patients with adenocarcinoma compared to patients with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent report, survival differences based on histology have been observed, and the adenocarcinoma subtype had a slightly longer survival rate 16 . They suggested that the introduction of endoscopic surveillance programs for Barrett's esophagus might explain the more pronounced improvement in survival among patients with adenocarcinoma compared to patients with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…5 The skin lesions may be observed in different locations of the human body. 2,[6][7][8][9][10][11][12][13] We describe 2 cases of cutaneous metastases in patients diagnosed with esophageal adenocarcinoma.…”
mentioning
confidence: 99%
“…In another study published in 1995, out of 838 patients with esophageal carcinoma, only two presented with metastatic disease to the skin [3]. Esophageal carcinoma metastasizing to the skin is very uncommon with only eight published case reports found in English literature to date (Table 1) [4][5][6][7][8][9][10][11]. Our case is unique in several ways.…”
Section: Discussionmentioning
confidence: 65%